2015
DOI: 10.1007/s11010-015-2429-8
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein inhibits prostate cancer cell growth and metastasis via the caveolin-1/AKT/mTOR pathway

Abstract: Prostate cancer (PCa) is lethal type of genitourinary cancer due to its high morbidity and gradual resistance to androgen deprivation therapy. Accumulating evidence has recently suggested that the daily intake of flavonoids is negatively correlated with the risk of cancer. In this study, we aimed to investigate the potential effects of baicalein on androgen-independent PCa cells and the underlying mechanisms through which baicalein exerts its actions. Cell viability and flow cytometric apoptosis assays indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 41 publications
(35 reference statements)
1
56
0
Order By: Relevance
“…Previous studies demonstrated that baicalein could exert its anti-tumor effect through modulating the PI3K/AKT signaling pathway in several cancer types [26-28]. To explore the effect of baicalein on PI3K/AKT pathway, the phosphorylation level of AKT at Thr308 and Ser473 in Bel-7402 cells treated with 0, 40 and 80 µM baicalein for 24 h was detected by western blotting, we found the phosphorylation level of AKT at both Thr308 and Ser473 were significantly decreased by baicalein treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that baicalein could exert its anti-tumor effect through modulating the PI3K/AKT signaling pathway in several cancer types [26-28]. To explore the effect of baicalein on PI3K/AKT pathway, the phosphorylation level of AKT at Thr308 and Ser473 in Bel-7402 cells treated with 0, 40 and 80 µM baicalein for 24 h was detected by western blotting, we found the phosphorylation level of AKT at both Thr308 and Ser473 were significantly decreased by baicalein treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Signaling pathways are involved in its function of anti-CRC, including activation of the Nrf2 signaling pathway [27] and attenuation of the MAPKs and PI3K-Akt activation [28]. As for other common malignant tumors, several reports have revealed various kinds of signal paths mediated by baicalein [8,29,30]. In the most important part of our research, we examined the proliferation of HCT116 cell periods by CCK-8 assay and flow cytometry (FCM).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that baicalein is closely related to osteoclast differentiation [6]. What's more, several studies have found that baicalein exerts antiinflammatory and anti-cancer effects in a broad spectrum of cancers [7].. For example, baicalein can induce apoptosis and inhibit metastasis of prostate cancer cells through inactivation of the caveolin-1/AKT/mTOR pathway [8]. Besides, it has been demonstrated that baicalein has efficient anticancer effects on hepatocellular carcinoma (HCC) to suppress cell growth and cell survival via the alteration of either microRNA [9] or mRNA expression profiles, the adjustment in the expression of CD24 included [10].…”
Section: Original Papermentioning
confidence: 99%
“…Baicalein is a flavone and an active ingredient in the traditional herb, Huang Qin. There is an accumulating amount of evidence that demonstrates baicalein’s role in treating and preventing various types of cancer [9,10,11,12,13,14,15]. In this review, we explored its chemical structure, properties, and possible biological mechanisms through which it acts.…”
Section: Introductionmentioning
confidence: 99%